Anti-tumor effect of α-pinene on human hepatoma cell lines through inducing G2/M cell cycle arrest - Weiqiang Chen; Ying Liu; Ming Li; Jianwen Mao; Lirong Zhang; Rongbo Huang; Xiaobao Jin; Lianbao Ye (Elsevier, 2015)
Pine needle oil from crude extract of pine needles has been used as an anti-cancer agent in Traditional Chinese Medicine. The α-pinene is a natural compound isolated from pine needle oil which has been shown anti-cancer activity. In previous study, we found that pine needle oil exhibited significant inhibitory effect on hepatoma carcinoma BEL-7402 cells. In this study, we investigate the inhibition of α-pinene on hepatoma carcinoma BEL-7402 cells in vitro and in vivo and further explore the mechanism. The results show that liver cancer cell growth was inhibited obviously with inhibitory rate of 79.3% in vitro and 69.1% in vivo, Chk1 and Chk2 levels were upregulated, CyclinB, CDC25 and CDK1 levels were downregulated.